2018
DOI: 10.22365/jpsych.2018.291.25
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems six-months after continuous earthquake activity in a Greek island

Abstract: Natural disasters, such as earthquakes, are traumatic events causing both acute and enduring stress to affected individuals. Psychosocial consequences include posttraumatic stress disorder (PTSD), reactions of anxiety and depression and sleep problems. The island of Cephalonia in Ionian Sea is characterized by its high seismic activity. More specifically, this activity has been considered to be the highest of the Balkan Peninsula and Europe in general. In January and February of 2014 a long sequence of earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Changes in employment status were due to earthquake-affected sleep states, although the difference in age distribution was considered. Previous studies have indicated that disasters largely altered the sleep conditions of the affected people [9][10][11]. As the analysis was based on cross-sectional data, there was a causative relationship between employment status and sleep conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in employment status were due to earthquake-affected sleep states, although the difference in age distribution was considered. Previous studies have indicated that disasters largely altered the sleep conditions of the affected people [9][10][11]. As the analysis was based on cross-sectional data, there was a causative relationship between employment status and sleep conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep status is an important factor closely related to mental health; sleep disturbances worsen mental health conditions, and vice versa [6][7][8]. Previous studies have also indicated that disasters affect the sleep status of the impacted people [9][10][11]. The effect of disasters on sleep status can be directly or indirectly (e.g., through altered mental health conditions) related to employment status, and changes in employment status after disasters can affect the sleep states of affected people.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of affected people of large-scale natural disasters have confirmed that sleep disorders are a common occurrence. Immediately after the earthquakes that occurred in Loma Prieta, California in 1989; 29 Hanshin-Awaji, Japan, in 1995; 3 Taiwan in 1999; 4 Athens, Greece, in 1999; 1 Sumatra, Indonesia, in 2004; 2 and Kefalonia Island, Greece, in 2014, 30 approximately 60% of the disaster affected people experienced insomnia symptoms and nightmares (after three to eight weeks). As our 2011 survey was conducted 4 months after the earthquake, the prevalence of insomnia symptoms was lower than that in the aforementioned studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the proportion of participants with insomnia was in our study as high as that of survivors of the GEJE who were additionally hit by a 15-m-high tsunami and was significantly higher than that of male workers under normal conditions. Earthquakes are traumatic events that cause acute and lasting stress to survivors [ 11 ]. The Kumamoto earthquake had frequent aftershocks [ 1 , 3 ] and Kumamoto City was very close to the epicentre at 4.4 km [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that mental health problems also occurred in survivors of the Kumamoto earthquake during the recovery period. However, there have been only a few studies on sleep problems among survivors after aftershocks lasting more than six months, with the exception of residents of a Greek island [ 11 ]. Therefore, their current situation should be analysed and mental health-related factors identified.…”
Section: Introductionmentioning
confidence: 99%